The pied piper of Hamelin - Andersen; Hans Christian (London Mind to Mind, 2010)
The tale is set in the town of Hamelin, which is overrun by a plague of rats. A mysterious Pied Piper, dressed in colorful clothes, offers to rid the town of the rats in exchange for a fee. After the townspeople refuse to pay him, the Piper uses his magical pipe to lead the children of Hamelin away, teaching the townsfolk a lesson about keeping promises and the consequences of deceit. This edition brings the timeless story to life with a captivating narrative and charming artwork.